1996
DOI: 10.1063/1.361210
|View full text |Cite
|
Sign up to set email alerts
|

Abinitio studies of S chemisorption on GaAs(100)

Abstract: Ab initio molecular orbital calculations are used to study S chemisorption on reconstructed GaAs(100) surfaces. Three cluster models are developed to simulate the main characteristics of 4×2, 4×6, and 2×6 reconstructed GaAs(100) surfaces. S atoms chemisorb preferentially on bridge sites and dramatically change the surface geometry. If a single S is adsorbed on a bridge site by breaking a Ga—Ga dimer bond, the Ga–Ga separation increases to 4.10 Å (from the dimerized separation of 2.80 Å), with a concomitant low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Defects owing to surface reconstruction are also termed intrinsic. Theoretical studies suggest that by occupying vacant coordination sites of surface atoms, adsorbates can induce surface atoms to adopt near-bulk coordination geometries; in some cases, this may even lead to removal of intrinsic surface states. In contrast, extrinsic surface states are new states introduced by foreign adsorbed material. These new states correspond to dangling bonds of the adsorbate, which energetically may lie within the band gap or overlap with continuum bulk states.…”
Section: B Analyte Binding:  Surface States and Orbital Considerationsmentioning
confidence: 99%
“…Defects owing to surface reconstruction are also termed intrinsic. Theoretical studies suggest that by occupying vacant coordination sites of surface atoms, adsorbates can induce surface atoms to adopt near-bulk coordination geometries; in some cases, this may even lead to removal of intrinsic surface states. In contrast, extrinsic surface states are new states introduced by foreign adsorbed material. These new states correspond to dangling bonds of the adsorbate, which energetically may lie within the band gap or overlap with continuum bulk states.…”
Section: B Analyte Binding:  Surface States and Orbital Considerationsmentioning
confidence: 99%
“…The origin of Ga 2 O 3 passivation mechanisms for reconstructed GaAs͑001͒ surface was investigated by using Ga 7 As 7 O 2 H 20 cluster model. 15 The simulation showed that the reduction in the density of surface states located within the bulk energy gap derives from initial near-bridgebonded O atoms. However, this cluster models could overestimate energy gap due to the strong quantum size effect of GaAs material.…”
Section: Introductionmentioning
confidence: 99%
“…Different sizes of clusters are used to represent the same surface because of non-uniqueness of a specific cluster to represent a surface and also to study dependence and convergence of cluster properties with respect to cluster sizes. As a comparison, Guo-Ping and Ruda [29] used a surface Ga-Ga dimer bond length of 2.80 Å in a similar ab initio cluster study of the adsorption of sulfur on the Ga-rich GaAs(100) surface. They used a Ga 7 As 7 H 20 cluster to represent the (4 × 2), (4 × 6), and (2 × 6) surfaces and found that S atoms chemisorbed preferentially on bridge sites.…”
Section: Computational Methodology and Resultsmentioning
confidence: 99%